2006
DOI: 10.35197/rx.02.01.2006.12.jg
|View full text |Cite
|
Sign up to set email alerts
|

Deterioro de semilla de dos procedencias de Swietenia macrophylla King., bajo distintos métodos de almacenamiento

Abstract: Se estudiaron en semilla de dos procedencias de Swietenia macrophylla King tres factores (contenido de humedad, envase, y almacenamiento) que podrían afectar su viabilidad, tomando como variable principal el porcentaje de germinación y relacionando éste con el contenido de humedad a través de tres períodos de almacenaje y los ácidos grasos al inicio y al final; la medición del contenido de humedad se llevó a cabo por el método convencional; la calidad de los ácidos grasos se llevó a cabo mediante la técnica de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…Likewise, Walters et al (2005) found similar results when they quantified fatty acids in sunflower seeds (Helianthus annuus L.) The fatty acids of cotyledons are predominantly linoleic and oleic acids. Also, Gómez-Tejero et al (2006) found a larger proportion of unsaturated fatty acids in seeds of Swietenia macrophylla King and other forest species.…”
Section: Fatty Acids Contentmentioning
confidence: 97%
“…Likewise, Walters et al (2005) found similar results when they quantified fatty acids in sunflower seeds (Helianthus annuus L.) The fatty acids of cotyledons are predominantly linoleic and oleic acids. Also, Gómez-Tejero et al (2006) found a larger proportion of unsaturated fatty acids in seeds of Swietenia macrophylla King and other forest species.…”
Section: Fatty Acids Contentmentioning
confidence: 97%
“…Mil., 2013). Regarding the mahogany seed, it is known that the seeds are rich in fats, however the advantage is that they contain a higher proportion of unsaturated fatty acids (Gómez et al, 2006) being beneficial to health. Regarding the mahogany seed it is known that the seeds are rich in fats, however the advantage is that it contains a higher proportion of unsaturated fatty acids (Reynoso et al, 2017), which are beneficial to health.…”
Section: Nutritional Composition Of the Extractsmentioning
confidence: 99%
“…En cuanto a los ácidos grasos, el linoleico fue el de mayor concentración (de 87 a 93 % del total), seguido del oleico (de 4.4 a 6.9 %), el palmítico (de 1.4 a 4.2 %) y del esteárico (de 0.6 a 2 %) (Cuadro 2, Figura 1); los dos primeros ácidos grasos son insaturados y los otros dos saturados. En semillas, los ácidos grasos insaturados se ubican primordialmente en la membrana celular (Walters et al, 2005;Gómez-Tejero et al, 2006;Panobianco y Vieira, 2007), por lo que se infiere que la mayor parte de los ácidos observados en las semillas analizadas, provienen de este tipo de membranas. Al respecto, Pérez-Camacho et al (2008) encontraron que el principal compuesto de reserva de la semilla de tomate de cáscara var.…”
Section: Fvunclassified